2010
DOI: 10.1260/0309-524x.34.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Nepalese Timber for Small Wind Turbine Blade Construction

Abstract: The paper describes the selection of Nepalese timber for development of small wind turbine blades on the basis of locally based low cost timbers, along with the selection of coatings to protect the timber from weathering. The selection criterion of timber includes timber mechanical properties, weathering effect on coatings, price, growth and availability of the timber. Mechanical properties such as Young's modulus of elasticity, breaking strength, breaking strain and Brinell's hardness of selected Nepalese tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In the simplest version, the blades can be carved from wooden parts, fully or in parts. Mishnaevsky Jr., Sinha et al [ 147 , 148 ] demonstrated the applicability of Nepali timber for low cost wind blades. The turbines with timber wind blades were installed on several locations around Nepal, and their usability was demonstrated (see Figure 10 ).…”
Section: Preventing Composite Wastes-2: Bio-based Compositesmentioning
confidence: 99%
“…In the simplest version, the blades can be carved from wooden parts, fully or in parts. Mishnaevsky Jr., Sinha et al [ 147 , 148 ] demonstrated the applicability of Nepali timber for low cost wind blades. The turbines with timber wind blades were installed on several locations around Nepal, and their usability was demonstrated (see Figure 10 ).…”
Section: Preventing Composite Wastes-2: Bio-based Compositesmentioning
confidence: 99%
“…In a number of works, the strength and damage mechanisms of hybrid composites were studied [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. It was reported, among others, that the incorporation of glass fibers in carbon fiber reinforced composites allows the improvement of their impact properties and tensile strain to failure of the carbon fibers.…”
Section: Composites For Wind Turbine Bladesmentioning
confidence: 99%
“…An interesting option for developing countries is small turbines, producible on-site, and made from “natural composites”, i.e., from locally available timber [ 47 ]. In a series of investigations, a group of Nepali, Danish and Australian scientists studied the applicability of different timbers for wind turbines, and demonstrated that the turbines with wooden blades represent a reliable and low cost option for the developing countries [ 48 , 49 , 50 , 51 ]. Figure 5 shows a test of a timber wind turbine blade and small wind turbines installed in a village school in Nepal.…”
Section: Composites For Wind Turbine Bladesmentioning
confidence: 99%
“…These blades were hand-carved and have large variations in mass and inertia, J . The limitation on length of solid timber blades is the cost of knot-free blanks, (Peterson and Clausen, 2004;Sinha et al ., 2010). There are complications; it is best, for example, to use timber quarter-sawn from well-seasoned logs (the main cuts being in the radial direction after the log has been quartered), which is not standard practice.…”
Section: Small Versus Large Bladesmentioning
confidence: 99%
“…Sinha et al (2010) tested a range of blade coating materials primarily for use in Nepal and found that enamel paint with a primer undercoat offered excellent surface protection.…”
Section: Timbermentioning
confidence: 99%